2007
DOI: 10.1007/s10735-007-9083-8
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins are upregulated in glandular epithelium at the time of implantation in the rat

Abstract: Regulation of luminal fluid is essential for blastocyst implantation. While it has been known for quite some time that there is a reduction in the amount of luminal fluid at the time of implantation, the mechanisms regulating this process are only just emerging. Previous studies have shown an upregulation of aquaporin (AQP) 5 channels in luminal epithelial cells at the time of implantation providing a mechanism for fluid reabsorption across the surface epithelium. However to date the contribution of fluid reab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Consistent with this, in this study, we showed the expression of AQP1 in the endothelial cells of the uterine blood vessels, whereas no expression was observed in the pig uterine epithelia or myometrium. The presence of AQP5 in the uterine epithelia has been previously shown in ovariectomized rats (Lindsay and Murphy 2006) and pregnant rats (Lindsay and Murphy 2007), as well as in mice during implantation (Richard et al 2003). Here, we report AQP5 expression in the myometrium and the luminal and glandular epithelium of the pig uterus.…”
Section: Aqps In Uterussupporting
confidence: 69%
See 1 more Smart Citation
“…Consistent with this, in this study, we showed the expression of AQP1 in the endothelial cells of the uterine blood vessels, whereas no expression was observed in the pig uterine epithelia or myometrium. The presence of AQP5 in the uterine epithelia has been previously shown in ovariectomized rats (Lindsay and Murphy 2006) and pregnant rats (Lindsay and Murphy 2007), as well as in mice during implantation (Richard et al 2003). Here, we report AQP5 expression in the myometrium and the luminal and glandular epithelium of the pig uterus.…”
Section: Aqps In Uterussupporting
confidence: 69%
“…Here, we report AQP5 expression in the myometrium and the luminal and glandular epithelium of the pig uterus. Lindsay and Murphy (2007) showed AQP9 expression in the apical plasma membrane of the glandular epithelium of the rat uterus. In this study, AQP9 protein was detected in the glandular epithelium and additionally in the luminal epithelium of the pig uterus.…”
Section: Aqps In Uterusmentioning
confidence: 94%
“…Subsequent studies have identified more than 10 different types of AQPs in mammals, found in several organs of different species, such as human kidney (Deen et al, 1994), rat epithelial tissue (Lindsay and Murphy, 2007), human blood vessels (Agre and Kozono, 2003), reproductive system of rodents (McConnell et al, 2002), dogs (Domeniconi et al, 2007), and pigs (Skowronski et al, 2009). The studies with AQP1 demonstrated that these proteins are small and integral membrane protein types, crossing the membrane from side to side, and containing two semipores that together form a water channel (Verkman and Mitra, 2000), assisting the transport of solutes (Thoroddsen et al, 2011).…”
Section: Aquaporinsmentioning
confidence: 99%
“…Among the AQPs found, nine isoforms have been expressed in the female reproductive system of humans, rats, and mice . Studies have demonstrated the expression of AQPs in the uterus of rats (AQPs 5 and 9, Lindsay and Murphy, 2007), mice (AQPs 0, 1, 4, and 5, Richard et al, 2003;AQPs 1, 3, and 8, Jablonski et al, 2003), pigs (AQPs 1, 5, and 9, Skowronski et al, 2009), and humans (AQPs 1-4, Thoroddsen et al, 2011). AQP1 expression was detected in the rat uterus, suggesting that these proteins represent a control system for water movement across the intraluminal, interstitial, and capillary compartments (Skowronski et al, 2009).…”
Section: Female Reproductive Systemmentioning
confidence: 99%
“…Among the possible candidates, two water channel genes, Aqp5 and Aqp 8, showed a simultaneous increase in expression levels. As aquaporin-mediated fluid transport is involved in a wide npg www.cell-research.com | Cell Research range of physiological and pathological conditions [11], and previous studies have shown that the expression of aquaporins is dynamically regulated in the uterus during pregnancy [12][13][14], we next examined the uterine expression levels of aquaporin family members in day-4 uteri (untreated, treated with E2 or ER antagonist ICI 182780) by RT-PCR analysis and confirmed the drastic increase in the expression levels of Aqp5 and Aqp8 after E2 treatment ( Figure 1J). A weak expression of Aqp5 was observed in the absence of E2 treatment, which was inhibited by ICI treatment ( Figure 1J).…”
mentioning
confidence: 99%